Critical Reynolds number in bifurcations / Numero de Reynolds Critico em Bifurcações - Amado, Flavio Peres (2020)
During the last four years, the authors and collaborators have been developing work to survey characteristics of thermal and fluid dynamics at the entrance of bifurcations under laminar regime. Equations were established that intend to predict the extension of the thermal and flow developing regions, depending on the variation of angles, flow rates and diameters, based on a CFD type simulation, which uses an in-house code employing finite difference method  and also through commercial softwares. This time, authors intend to increase the knowledge about flow in bifucations by raising equations that predict the Critical Reynols Number. The specialized literature states that the Critical Reynols Number for toroidal and helical geometries is a function of the radius of curvature and the inner radius of the tube that makes up these structures. In the presente work, this equation format was customized for bifurcations, similar to the manner the authors employed in them previous articles. As a bifurcation has no radius of curvature, each outlet is considered to be an approximately toroidal curve, with a radius calculated according to the formulation proposed also in previous papers by the authors. The correlation achieved is based solely on numerical simulation results. The velocity values from which the flow changed from laminar to turbulent were noted and used to calculate the respective Reynolds Number values. Such data were gathered to establish an expression that exclusively served the sample universe of this research. However, consistent experimental results are expected for future works in which it is intended to confirm the conclusions previously established from computer simulation